Supply Chain Integration and Supply Chain Performance: The Mediating Role of Supply Chain Resilience - Arsalan Zahid Piprani; Suhana Mohezar; Noor Ismawati Jaafar (International Journal of Supply Chain Management, 2020)
The objective of this study is to examine the influence of supply chain integration (SCI) on supply chain resilience (SCRES) on supply chain performance (SCP) dimensions of large – scale manufacturing firms in Pakistan. It also examines the indirect effects of all the SCI dimensions on all the SCP dimensions through the SCRES. A quantitative approach using questionnaire survey was employed to examine the hypotheses and theoretical framework. Data were collected from 182 manufacturing firms in Pakistan and the SMART PLS version 3.2.7 was used for data analysis. The results showed that the SCI contributed significantly to the SCRES while the SCRES impacted on the SCP substantially. However, the association between the SCI and the SCP was not linear; it was determined by the level of the SCRES. This study fills the research gap by integrating the SCRES as a mediator between the SCI and the SCP.